Role of Circulating Exosomes in Cerebrovascular Diseases: A Comprehensive Review - Lu, Zhiwen; Tang, Haishuang; Li, Sisi; Zhu, Shijie; Li, Siqi; Huang, Qinghai (Current Neuropharmacology, 2023)
Exosomes are lipid bilayer vesicles that contain multiple macromolecules secreted by the parent cells and play a vital role in intercellular communication. In recent years, the function of exosomes in cerebrovascular diseases (CVDs) has been intensively studied. Herein, we briefly review the current understanding of exosomes in CVDs. We discuss their role in the pathophysiology of the diseases and the value of the exosomes for clinical applications as biomarkers and potential therapies.
Keywords: cerebrovascular disease